Winter population estimates and distribution changes of two common East Asian dabbling duck species: current status and long-term (1990–2020) trends - Zhang, Beixi; Meng, Fanjuan; Tung, Yat; Kim, Eun-Jung; Zheng, Dingtuan; Yang, Jin; Han, Yongxiang; Liu, Yang; Zhu, Shuyu; Li, Jing; et al. (Wildfowl, 2023)
Based on survey data from China and Asian Waterbird Census (AWC) data from 14 other countries, the population status and trends of Eurasian Wigeon Mareca penelope and Northern Pintail Anas acuta (hereafter Wigeon and Pintail, respectively) using the East-Asia Australasia Flyway (EAAF) were estimated for the first time for the 1990s–2020s. In contrast to earlier assessments, more than 98% of the EAAF estimated numbers of Wigeon and Pintail were found to be present in East Asia, with very few counted in Southeast Asia. Their winter abundances were estimated at 250,000 and 220,000 (150,000 and 160,000 in Japan; 90,000 and 50,000 in China; 5,000 and 6,000 in South Korea), respectively in the early 2020s. These current totals compare with the Waterbird Population Estimates (WPE5) of Wetlands International of 500,000–1,000,000 for Wigeon and 200,000–300,000 for Pintail. In the past 30 years, total numbers of both species in East Asia initially decreased and then stabilised, during which time the number of internationally important wintering sites (holding more than 1% of the flyway population) decreased. The majority of Wigeon (73%) and Pintail (87%) were formerly found in coastal areas, where both species have showed significant declines in areas such as the Jiangsu coast, China. Wintering numbers of Wigeon inland increased, while those of Pintail declined. At present, the nine internationally important wintering sites for Wigeon are situated between 36°N and 22°N, while the 26 internationally important wintering areas for Pintail occur at 40°N–22°N. Wintering numbers of both species in Japan are mainly distributed in the south of Hokkaido, whereas in China both species mainly occur in the Yellow River estuary, in southern coastal areas, and along the Yangtze River. In Korea, Pintail are largely restricted to Asan Bay. Based on these results, we draw attention to the urgent need for wetland conservation in China and South Korea to protect both species effectively, and for updated estimates of the numbers of Wigeon and Pintail in Southeast Asia, which in both cases are fewer than 1,000 birds rather than the 80,000 and 20,000 previously estimated.